2018
DOI: 10.1002/adfm.201707551
|View full text |Cite
|
Sign up to set email alerts
|

Polyformamidine‐Derived Non‐Noble Metal Electrocatalysts for Efficient Oxygen Reduction Reaction

Abstract: A facile approach for the template‐free synthesis of highly active non‐noble metal based oxygen reduction reaction (ORR) electrocatalysts is presented. Porous Fe−N−C/Fe/Fe3C composite materials are obtained by pyrolysis of defined precursor mixtures of polyformamidine (PFA) and FeCl3 as nitrogen‐rich carbon and iron sources, respectively. Selection of pyrolysis temperature (700–1100 °C) and FeCl3 loading (5–30 wt%) yields materials with differing surface areas, porosity, graphitization degree, nitrogen and iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…24 The resulting nL values were found to be 2.1 ± 0.1 for the less active catalysts (C and Bipyr/C) and ∼2.7 for the Co-N/C cata-lysts. As already discussed in our previous work as well as by other 4,24,[40][41][42] this means the addition of both a transition metal and nitrogen creates new active sites which promote either the direct re-duction of oxygen to water or the 2 + 2-electron pathway. Despite the large increase in activity, the synthesized Co-N/C catalysts are still notably less active than the commercial Pt/V catalyst which displays a half-wave potential of 0.83 V vs RHE and a high electron transfer number of 3.8 ± 0.1.…”
Section: Table II N2 Sorption Analysis Datasupporting
confidence: 55%
“…24 The resulting nL values were found to be 2.1 ± 0.1 for the less active catalysts (C and Bipyr/C) and ∼2.7 for the Co-N/C cata-lysts. As already discussed in our previous work as well as by other 4,24,[40][41][42] this means the addition of both a transition metal and nitrogen creates new active sites which promote either the direct re-duction of oxygen to water or the 2 + 2-electron pathway. Despite the large increase in activity, the synthesized Co-N/C catalysts are still notably less active than the commercial Pt/V catalyst which displays a half-wave potential of 0.83 V vs RHE and a high electron transfer number of 3.8 ± 0.1.…”
Section: Table II N2 Sorption Analysis Datasupporting
confidence: 55%
“…15−17 Specifically, various transition-metal−nitrogen−carbon catalysts have been extensively pursued due to their low cost, minimal environmental impact, and satisfactory performance. 18,19 Generally, according to the different precursors, the synthetic methods of transition-metal−nitrogen−carbon catalysts can be categorized as follows: (i) pyrolyze the metal and carbon co-containing complexes. For example, Mullen et al 20 synthesized carbon-supported Fe 3 O 4 catalysts by the pyrolysis of Fe-ion-containing porous graphene oxide aerogels at 600 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel cells and metal–air batteries have attracted more attention for application in various energy-related fields in the future; however, the slow cathodic oxygen reduction reaction (ORR) has limited their improvement. Hence, high activity and long stability of the ORR electrocatalysts are urgently needed for practical application of these devices on a large scale. Platinum-based metals have long been regarded as the best electrocatalysts. However, their high cost, limited reserve, weakness to fuel crossover, and poor stability have hindered their commercial application. Recently, various nonprecious-metal catalysts have been explored to substitute noble-metal platinum catalysts for boosting the ORR. Specifically, various transition-metal–nitrogen–carbon catalysts have been extensively pursued due to their low cost, minimal environmental impact, and satisfactory performance. , …”
Section: Introductionmentioning
confidence: 99%
“…A series of porous FeÀ NÀ C/Fe/Fe 3 C nanocomposites have been synthesized in the temperature range of 700-1000 °C and 5-30 wt% loading of FeCl 3 with differing porosity, surface areas, graphitization degree as well as varying iron and nitrogen content to study ORR. [42] Similarly, FeÀ NÀ C electrocatalyst was synthesized based on modified graphene from the mixture of Fe salt and graphitic carbon nitride (g-C 3 N 4 ) formed by heat treatment. The resultant electrocatalyst exhibited high mass activity, excellent stability in acidic media over 70 h. [43] Nitrogen-modified carbon-based electrocatalyst with varying amounts of Co or Fe contents revealed that these metals boost the formation of active sites by introducing nitrogen into the graphene layers during pyrolysis.…”
Section: Role Of Non-noble Metalsmentioning
confidence: 99%
“…Metal‐nitrogen‐carbon electrocatalysts are widely known due to their encouraging ORR activity and stability. A series of porous Fe−N−C/Fe/Fe 3 C nanocomposites have been synthesized in the temperature range of 700–1000 °C and 5–30 wt% loading of FeCl 3 with differing porosity, surface areas, graphitization degree as well as varying iron and nitrogen content to study ORR [42] . Similarly, Fe−N−C electrocatalyst was synthesized based on modified graphene from the mixture of Fe salt and graphitic carbon nitride (g‐C 3 N 4 ) formed by heat treatment.…”
Section: Introductionmentioning
confidence: 99%